2010
DOI: 10.2967/jnumed.109.070425
|View full text |Cite
|
Sign up to set email alerts
|

PET/CT with 18F-FLT: Does It Improve the Therapeutic Management of Metastatic Germ Cell Tumors?

Abstract: Because 18 F-FDG PET alone has only limited value in metastatic germ cell tumors (GCTs), we investigated the addition of 39-deoxy-39-18 F-fluorothymidine (FLT) to 18 F-FDG for early response monitoring and prediction of the histology of residual tumor masses in patients with metastatic GCT. Methods: Eleven patients with metastatic GCT were examined with both 18 F-FDG PET/CT and 18 F-FLT PET/CT before chemotherapy, after the first cycle of chemotherapy (early response), and 3 wk after completion of chemotherapy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 34 publications
0
25
0
Order By: Relevance
“…In this context, Pfannenberg et al (27) report in this issue of The Journal of Nuclear Medicine the results of an important study comparing 18 F-FDG and 18 F-FLT PET for monitoring tumor response to chemotherapy in metastatic germ cell tumors (GCTs). GCTs are generally classified as seminomas or nonseminomas; each of these subtypes comprises approximately 50% of cases (28).…”
Section: F-flt and F-fdg Pet In Metastatic Gctmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, Pfannenberg et al (27) report in this issue of The Journal of Nuclear Medicine the results of an important study comparing 18 F-FDG and 18 F-FLT PET for monitoring tumor response to chemotherapy in metastatic germ cell tumors (GCTs). GCTs are generally classified as seminomas or nonseminomas; each of these subtypes comprises approximately 50% of cases (28).…”
Section: F-flt and F-fdg Pet In Metastatic Gctmentioning
confidence: 99%
“…Pfannenberg et al (27) performed 18 F-FLT PET and 18 F-FDG PET scans on a group of 11 patients with GCT (10 nonseminomas and 1 seminoma).…”
Section: F-flt and F-fdg Pet In Metastatic Gctmentioning
confidence: 99%
“…Although there was a trend toward increased 18 F-FLT uptake and Ki-67 index in malignant tissues, there has been considerable overlap and further studies will be needed to assess the feasibility of this technique in differentiating benign from malignant ovarian tissues. Clinical studies in germ cell tumors that have evaluated 18 F-FLT and 18 F-FDG to assess lesions for residual disease have shown limited benefits (60), probably more because of the lower uptake and sensitivity of 18 F-FLT in detecting tumors due to lower proliferation (61). Clinical studies are needed to assess 18 F-FLT PET applications in testicular cancers.…”
Section: Genitourinary Cancersmentioning
confidence: 99%
“…In a recent study comparing 39-deoxy-39-18 Ffluorothymidine ( 18 F-FLT) and 18 F-FDG for therapy monitoring in 11 nonseminomatous germ cell tumor (NSGCT) patients, Pfannenberg et al (1) reported 2 patients in whom resected residual masses contained mature teratoma and harbored a low 18 F-FLT uptake (mean standardized uptake value [SUV mean ], 1.4 and 0.8) similar to that observed in 2 patients with necrosis (SUV mean , 1.3 and 1.3).…”
Section: To the Editormentioning
confidence: 99%